Childhood vulval lichen sclerosus in a patient with ectodermal dysplasia and uncombable hair. - Powell, J; Wojnarowska, F; Dawber, R; Slavotinek, A; Huson, S (1998)
An 11-year-old girl was diagnosed as having ectodermal dysplasia, with abnormalities of her nails, teeth, and hair noted from infancy. Her hair was unruly and investigations confirmed the changes seen in "cheveux incoiffables"-the uncombable hair syndrome. She also had atopy requiring treatment to control asthma and eczema. When she was 8 years old she developed vulval lichen sclerosus, which was controlled easily with early treatment. The coexistence of these conditions is discussed.